2004
DOI: 10.1063/1.1786654
|View full text |Cite
|
Sign up to set email alerts
|

Structural and optical properties of Ba(Cox,Ti1−x)O3 thin films fabricatedby sol-gel process

Abstract: Ba ( Co x , Ti 1 − x ) O 3 thin films were prepared on fused quartz substrate by a sol-gel method. The results of x-ray diffraction showed that the films are perovskite phase and the change of lattice constant caused by different Co concentration is undetectable. Optical transmittance measurement indicated that Co doping has effect on the energy band structure. The energy gap of Ba(Cox,Ti1−x)O3 decreased linearly with the increase of Co concentration. It is inferred that the energy level of conduction bands de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
10
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 19 publications
3
10
0
Order By: Relevance
“…4 On the other hand, optimal cation doping ͑Ti 4+ ͒ is a widely accepted approach to tailor the physical properties, such as transition temperature, ferroelectric characteristics, and dielectric properties. Recently, perovskite ferroelectric film materials have received much attention in view of their wide applications in dynamic random access memories, electro-optic switches, pyroelectric detectors, optical modulators, and mixers.…”
Section: Composition Dependence Of Dielectric Function In Ferroelectrmentioning
confidence: 99%
“…4 On the other hand, optimal cation doping ͑Ti 4+ ͒ is a widely accepted approach to tailor the physical properties, such as transition temperature, ferroelectric characteristics, and dielectric properties. Recently, perovskite ferroelectric film materials have received much attention in view of their wide applications in dynamic random access memories, electro-optic switches, pyroelectric detectors, optical modulators, and mixers.…”
Section: Composition Dependence Of Dielectric Function In Ferroelectrmentioning
confidence: 99%
“…Ferroelectric thin films have great applications in electro-optic devices, nonvolatile memory, and dynamic access memory [1,2]. Various methods, both vacuum-based and non-vacuum based techniques, such as pulse laser deposition (PLD), metalorganic chemical-vapor deposition, sol-gel processing, and streaming process for electrodeless electrochemical deposition (SPEED), have been employed in fabricating epitaxial and polycrystalline films [3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…13 However, when Co is substituted, the band gap decreases with increasing Co concentration ͑x = 0.01-0.10͒. 14 In a previous study, we explored the effects of substituting another transition metal, Pd, into BaCeO 3 and found that the presence of Pd stabilized by an O-vacancy decreased the band gap significantly by creating a stable square-pyramidal Pd complex. 15,16 Although BaCe 1−x Pd x O 3 is not ferroelectric, solid solutions of Ba͑Ti 1−x Ce x ͒O 3 have been synthesized and are reported to demonstrate ferroelectric responses.…”
Section: Introductionmentioning
confidence: 99%